Time‐dependent risk of depression, anxiety, and stress‐related disorders in patients with invasive and in situ breast cancer. Issue 4 (25th November 2016) - Yang, Haomin; Brand, Judith S.; Fang, Fang; Chiesa, Flaminia; Johansson, Anna L.V.; Hall, Per; Czene, Kamila
Abstract : Despite concerns about the mental health of breast cancer patients, little is known regarding the temporal risk pattern and risk factors of common mental disorders among these patients. We estimated standardized incidence ratios (SIRs) of depression, anxiety and stress‐related disorders in a Swedish nationwide cohort of 40, 849 women with invasive and 4, 402 women with in situ breast cancer (2001–2010, median follow‐up = 4.5 years). The impact of patient, tumor and treatment characteristics was analyzed using flexible parametric survival models in a regional cohort of 7, 940 invasive breast cancer patients (2001–2013, median follow‐up = 7.5 years). Women with invasive breast cancer showed increased rates of depression, anxiety and stress‐related disorders [overall SIR (95% CI) = 1.57 (1.46–1.69), 1.55 (1.43–1.68) and 1.77 (1.60‐1.95), respectively]. SIRs were highest shortly after diagnosis, but remained increased up to 5 years. Younger age at diagnosis, comorbidity, higher‐grade disease, lymph node involvement and chemotherapy were independently associated with the risk of depression and anxiety in invasive cancer patients, with chemotherapy and higher‐grade disease conferring short‐term risk only, while comorbidities were mainly associated with late‐onset events. No clinical risk factors were identified for stress‐related disorders except for a greater risk associated with younger age. Patients with in situ cancer only showed an increased incidence of stress‐related disorders during the first 6 months after diagnosis [SIR (95% CI) = 2.76 (1.31‐5.79)]. The time‐dependent risk profile of invasive cancer patients may guide health care professionals for timely and targeted psycho‐oncologic interventions. Abstract : What's new? The burden of invasive breast cancer is great, and today increasing numbers of patients are at elevated long‐term risk of anxiety, depression, and stress‐related disorders. The present study shows that risk of such disorders is highest shortly after diagnosis, particularly among young breast cancer patients who present with aggressive tumor characteristics and are undergoing chemotherapy. Risk remains elevated for up to 5 years in these patients. Among in situ breast cancer patients, increased risk occurs only within the first 6 months of diagnosis. The findings highlight the importance of timing for psycho‐oncologic interventions targeted to invasive breast cancer patients.